A multifunctional sustainable ionohydrogel with excellent low-hysteresis-driven mechanical performance, environmental tolerance, multimodal stimuli-responsiveness, and power generation ability for wearable electronics. Issue 34 (11th August 2022) - Si, Wanjie; Liang, Yingpei; Chen, Yukun; Zhang, Shuidong
Abstract : The defects of conductive hydrogels, such as high internal friction, poor performance at freezing temperatures, and evaporation during long-term storage, restrict their application in wearable electronics. Abstract : The defects of conductive hydrogels, such as high internal friction, poor performance at freezing temperatures, and long-term evaporation during storage, restrict their application in wearable electronics. Herein, a dual-crosslinked starch/PAM/borax/glycerol ionohydrogel is fabricated through a one-pot gelation-assisted polymerization approach. Starch supports PAM adapting to the glycerol/water binary solvent system through hydrogen-bonding interactions and graft copolymerization, while boronic ester linkages serve as cross-linking sites. Interestingly, the ionohydrogel exhibits extremely low internal friction (0.5 kJ m −3 ) and excellent environmental tolerance over a wide temperature range (−60–80 °C). Strikingly, the ionization of Na2 B4 O7 is sensitive to variations in temperature and humidity in a binary solvent system, which also facilitates the ionohydrogel achieving a lower freezing point and higher evaporation temperature. The ionohydrogel achieves appreciable conductivity (21.1 mS m −1 ) and good mechanical properties (tensile strength: 332 kPa; elongation at break: 514%) at −40 °C. Taking advantage of these exceptional characteristics and stable transport channels for Na + and B(OH) 4−, an assembled sensor can effectively detect variations in humidity (20–98%), temperature, and strain with high sensitivity, simulating the sensitivity of human skin. It is noteworthy that a single-electrode TENG manufactured using the ionohydrogel displays excellent energy-harvesting capabilities under different types of deformation. This work provides an effective strategy for obtaining a multifunctional ionohydrogel with high Δ R / R 0 sensitivity for utilization in self-powered wearable electronics under extreme environmental conditions.